Clinico-Haematological Alterations in Goats Affected with Ruminal Acidosis - Chavelikar, PR; Mandali, GC; Patel, DM (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
Ruminal acidosis is one of the most important clinical emergencies in sheep and goats resulting into high mortality rate. In the present study, eight healthy farm goats and 24 goats presented to the TVCC of the college with clinical signs of ruminal acidosis like anorexia, tympany, increased pulse and respiratory rate, reduced body temperature, doughy rumen, enteritis, oliguria, grinding of teeth, purulent nasal discharge, muscle twitching, arched back, dehydration and recumbency with rumen liquor pH below 6 were examined for haematological alterations using autohaematoanalyzer. Among various haematological parameters evaluated from acidotic goats, the mean values of Hb (12.21±0.17 vs. 10.86±0.15 g/dl), TEC (14.28±0.16 vs. 12.04±0.36 ×106/ μl), TLC (13.43±0.11 vs. 11.11±0.27 ×103/μl), PCV (36.91±0.53 vs. 29.88±0.55%), neutrophils (64.54±0.93 vs. 28.13±0.92%), MCV (23.38±0.37 vs. 19.38±1.34 fl) and MCH (7.03±0.08 vs. 6.31±0.25 pg) were found significantly increased, while the mean values of lymphocytes (28.00±0.82 vs. 65.38±0.80%) and MCHC (24.55 ±0.26 vs. 34.88±0.97 g/dl) were decreased significantly from the base values of healthy goats. It was concluded that ruminal acidosis induced due to accidental heavy ingestion of readily fermentable carbohydrate rich grains and food waste significantly altered the haematological profile concurrent with clinical manifestations in goats, and hence can be used to assess the severity of the disease.